RELASI POLITIK BIROKRASI DAN PERUSAHAAN PERKEBUNAN PT. JHONLIN BATU MANDIRI DI KABUPATEN BOMBANA - Asriani; La Ode Muhammad Elwan; Dhani Himawan (Halu Oleo University, 2023)
The purpose of writing this article is to find out the relationship between the bureaucracy and the company PT. Jhonlin Batu Mandiri in Bombana Regency. The research method used is a qualitative research type with a descriptive approach. The data analysis technique uses the opinion of Miles, Huberman & and Saldaña (2014) with an interactive model starting from data collection, data reduction, data presentation, and conclusions. Based on the results that have been obtained regarding bureaucratic relations and plantation companies which result in power politics in local government agencies that collaborate with entrepreneurs through clientelistic relations and market relations. As a result, in the regional relations position, bureaucratic and company cooperation occurred for the benefit of village infrastructure development, and in the market relations position, there was a claim for community plantation land from PT. Jhonlin Batu Mandiri in Tinabite Village, Lantari Jaya District, Bombana Regency. Market relations are short-term relations that are developed through the issue of company political promises to land owners, resulting in supply and demand